A Case of Mycobacterium riyadhense in an Acquired Immune Deficiency Syndrome (AIDS) Patient with a Suspected Paradoxical Response to Antituberculosis Therapy - Maged Omar Al-Ammari; Samar Assem Badreddine; Hani Almoallim (Case Reports in Infectious Diseases)
A 30-year-old male patient with acquired immune deficiency syndrome (AIDS) on highly active antiretroviral therapy (HAART) presented with clinical picture suggestive of pulmonary tuberculosis. He was commenced on antituberculosis therapy (ATT) with signs of improvement. Then he developed cervical lymph node abscess which was drained. Steroid was started for presumed paradoxical response to ATT which results in clinical regression. The culture result revealed Mycobacterium riyadhense. This report addresses the rarity of this bacteria in medical literature. It reviews clinical presentations and medical treatment particularly in the setting of coinfections.